Electric Mars: A large trans‐terminator electric potential drop on closed magnetic field lines above Utopia Planitia. Issue 2 (10th February 2017) - Collinson, Glyn; Mitchell, David; Xu, Shaosui; Glocer, Alex; Grebowsky, Joseph; Hara, Takuya; Lillis, Robert; Espley, Jared; Mazelle, Christian; Sauvaud, Jean‐André; Fedorov, Andrey; Liemohn, Mike; et al.
Abstract: Parallel electric fields and their associated electric potential structures play a crucial role in ionospheric‐magnetospheric interactions at any planet. Although there is abundant evidence that parallel electric fields play key roles in Martian ionospheric outflow and auroral electron acceleration, the fields themselves are challenging to directly measure due to their relatively weak nature. Using measurements by the Solar Wind Electron Analyzer instrument aboard the NASA Mars Atmosphere and Volatile EvolutioN (MAVEN) Mars Scout, we present the discovery and measurement of a substantial (ΦMars =7.7 ± 0.6 V) parallel electric potential drop on closed magnetic field lines spanning the terminator from day to night above the great impact basin of Utopia Planitia, a region largely free of crustal magnetic fields. A survey of the previous 26 orbits passing over a range of longitudes revealed similar signatures on seven orbits, with a mean potential drop (ΦMars ) of 10.9 ± 0.8 V, suggestive that although trans‐terminator electric fields of comparable strength are not ubiquitous, they may be common, at least at these northerly latitudes. Key Points: We report the discovery of a substantial parallel electric potential drop on closed day‐to‐night magnetic field lines at Mars Although trans‐terminator electric fields are not ubiquitous, they may be common in the northern Martian hemisphere Observations are consistent with a transient or localized phenomenon and may be associated with magnetic crustal field remanents